Data Platform for the Research and Prevention of Alzheimer’s Disease - An, Ning; Jin, Liuqi; Yang, Jiaoyun; Yin, Yue; Jiang, Siyuan; Jing, Bo; Au, Rhoda (Advances in experimental medicine and biology, 2017)
With the rapid increase in global aging, Alzheimer’s disease has become a major burden in both social and economic costs. Substantial resources have been devoted to researching this disease, and rich multimodal data resources have been generated. In this chapter, we discuss an ongoing effort to build a data platform to harness these data to help research and prevention of Alzheimer’s disease. We will detail this data platform in terms of its architecture, its data integration strategy, and its data services. Then, we will consider how to leverage this data platform to accelerate risk factor identification and pathogenesis study with its data analytics capability. This chapter will provide a concrete pathway for developing a data platform for studying and preventing insidious onset chronic diseases in this data era.